A preliminary prediction of seismic damage based degradation in RC structures. - Gupta, Vinay K.
Estimation of structural damage from a known increase in the fundamental period of a structure after an earthquake or prediction of degradation of stiffness and strength for a known damage requires reliable correlations between these response functionals. This study proposes a modified Clough-Johnston single degree of freedom oscillator to establish these correlations in the case of a simple elasto plastic oscillator. It is assumed that the proposed oscillator closely models the response of a given multi degree of freedom system in its fundamental mode throughout the duration of the excitation. The proposed model considers the yield displacement level and ductility supply ratio related parameter as two input parameters which must be estimated over a narrow range of ductility supply ratio from a frequency degradation curve. This curve is to be identified from a set of recorded excitation and response time histories. Useful correlations of strength and stiffness degradation with damage have been obtained wherein a simple damage index based on maximum and yield displacements and ductility supply ratio has been considered. As an application, the proposed model has been used to demonstrate that ignoring the effects of aftershocks in the case of impulsive ground motions may lead to unsafe designs.
Keywords: Reinforced concrete structures; Clough-Johnston oscillator; Stiffness degradation; Strength degradation; Damage index; Effects of aftershocks